Analysis of Class VII Students' Experiences in the Implementation of the Two Stay Two Stray Learning Model in the Nahwu Subject at Daarul Huffaadz Alfalahiyah Islamic Boarding School: Analisis Pengalaman Belajar Siswa dalam Penerapan Model Pembelajaran Two Stay Two Stray pada Mata Pelajaran Nahwu - Muhamad Agung Mulyawan; Eka Setiawati; Ahmad Adam Mazidan (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2025)
This article analyzes the experiences of seventh-grade students in the implementation of the Two Stay Two Stray (TSTS) learning model in the Nahwu subject at Daarul Huffaadz Alfalahiyah Islamic Boarding School. The study aims to evaluate the effectiveness of the TSTS model in enhancing student engagement and comprehension of Nahwu material, which has often been perceived as difficult and tedious by many students. The research employs a descriptive qualitative method, with data collected through interviews with students and classroom observations. The findings reveal that the majority of students experienced a significant improvement in their understanding of Nahwu after the application of the TSTS model. Students reported feeling more active and involved in the learning process, particularly due to the opportunity to discuss, express opinions, and explain material to their peers. One student stated, “After participating in Nahwu learning with the TSTS model, I feel very happy and more confident. This method made learning more interactive and enjoyable.” In addition to improving comprehension, the model also helps develop students' communication and collaboration skills. Observations indicated that student interactions became more dynamic compared to traditional teaching methods. The teacher's role as a facilitator, guiding discussions without dominating them, aligns with constructivist principles, which emphasize the importance of social interaction in the learning process. Key factors that support the success of this model include student readiness, teacher support, and a conducive learning environment. However, challenges remain, such as the model’s dependence on effective student collaboration, which needs to be carefully managed. Keywords: Learning Model, Nahwu, Studentd Experiences, Two Stay Two Stray (TSTS).